Empirical study on the use of puzzle games for improving Chinese character acquisition of non-native learners of Chinese language / Shakerin Ismail, Mohd Rashdan Sallehuddin and Ho Yong Zhou - Soon, Goh Ying; Yeng, Yee Leong (2015)
This study was to find out the effects of students’ engagement in Chinese character puzzle game on language acquisition. The study was conducted on students of the first level of Chinese beginner course at UiTM (Terengganu) in Malaysia. To accomplish the purpose of the study, the researchers chose a sample of 30 subjects, who were taking Chinese beginner course and at the same time participated in a Chinese character puzzle game competition. The subjects were asked to fill up online questionnaire on their benefits gained after the competition. The result indicated positive perceptions among the learners. It was concluded that the subjects who participated in puzzle game, viewed this activity can act as a tool to assist them to recognize more Chinese characters.